Kinetic studies of catalytic ozonation of atrazine - Tepuš, Brigita (Array, 2008)
Abstract: The aim of our work was to degrade atrazine by the ozone treatment of both a model and the original drinking water samples, using Pt-catalyst, and to evaluate the performance of this catalyst. The rate constant for the reaction of atrazine with ozone was determined in the model water sample. The activation energies and the reaction orders of ozone decomposition were determined in both the model and the drinking water samples. Ozone treatment using Pt-catalyst has some influence on the loss of atrazine in the sources of drinking water. The concentration of some metabolites in the model and drinking water was observed during ozone treatment. The toxicity of atrazine to crustacean Daphnia magna in the original drinking water and in the ozone treated water samples was also assessed